Latihan Dasar Kepemimpinan untuk Penguatan Jiwa Kepemimpinan pada Ikatan Pelajar Muhammadiyah - Bahtiar Effendi; M Fathrezza Imani (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This community service activity aims to provide leadership provisions for organizational members, as well as provide education about the role of each member for the progress of the organization. The target of this activity is the leadership and members of the Muhammadiyah Student Association (IPM) Twigs of SMK Muhammadiyah 1 Pemalang with a total of about 50 participants. The implementation of this activity uses a training approach that combines education, as well as interactive discussions. The results of this activity help strengthen the leadership spirit of the leaders and members of the IPM organization so that they are able to hold firm the mandate in the organization and be able to carry out duties and responsibilities according to their respective roles.